2017
DOI: 10.1002/aqc.2817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of translocation on survival and growth of freshwater mussels within a West Gulf Coastal Plain river system

Abstract: Human‐mediated threats have led to the rapid decline of species inhabiting freshwater ecosystems, and among the groups most affected are freshwater mussels of the family Unionidae. As a result, species translocation is increasingly used in conservation programmes, yet experimental evidence documenting the success of this strategy is limited. The goal of this study was to examine the effects of translocation on survival probability, shell growth and body condition of a state‐threatened (Quadrula houstonensis) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…The data from located and identified individuals indicate that the short‐term mortality of mussels translocated during this study was minimal, ranging from 0 (first trial) to 3% (second trial). High survival rates (>80%) of translocated and individually marked mussels were reported previously by Cope et al () and by Tsakiris, Randklev, Blair, Fisher, and Conway (). A much higher mortality rate was expected during the second trial, however, because the habitat had been destroyed by the flood (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…The data from located and identified individuals indicate that the short‐term mortality of mussels translocated during this study was minimal, ranging from 0 (first trial) to 3% (second trial). High survival rates (>80%) of translocated and individually marked mussels were reported previously by Cope et al () and by Tsakiris, Randklev, Blair, Fisher, and Conway (). A much higher mortality rate was expected during the second trial, however, because the habitat had been destroyed by the flood (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…While some studies have found only minimal effects of translocation on survival of freshwater mussels 21 , 22 , this practice often results in increased mortality and/or reduced growth rates 19 , 23 25 . However, models of future extinction rates predict that, without effective intervention, more than 40% of North American freshwater mussel species will become extinct over the next 100 years 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Translocation of individual mussels between sites has been shown to be an effective tool in other unionid conservation efforts, with studies showing low mortality and limited effects on mussel growth when placed in suitable and functional habitats (Tsakiris, Randklev, Blair, Fisher, & Conway, 2017; Zając et al, 2019). Transfer of adult M. margaritifera individuals from one body of water to another, however, has been shown to be an ineffective conservation tool (Buddensiek, 1995; Cosgrove & Hastie, 2001; Preston, Keys, & Roberts, 2007), with a study in Massachusetts showing nearly 100% mortality after relocation (Cope & Waller, 1995).…”
Section: Discussionmentioning
confidence: 99%